Internalisasi Nilai-Nilai Pendidikan Akhlak melalui Program “Brascho Nyantrik” di SMA Brawijaya Malang - Alfaridzih, Achmad; Akbar, Ahmad Faidhullah; Najikh, Akhmad; Faslah, Romi (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The decline in morals forces every institution to develop new solutions and ideas to overcome this problem. This research aims to explain how the process, values and results of internalization of moral education occur in the "Brascho Nyantrik" program at SMA Brawijaya Malang. The research method applied is qualitative-descriptive using interviews, observation and documentation. Research findings include the internalization process through a series of activities in the program, which is supported by the learning process in the classroom. Internalized moral values include courtesy, sincerity, gratitude, work ethic, patience, discipline, obedience, manners in dress, honesty, respect for others, and a spirit of mutual cooperation. This program has an impact on improving individual attitudes and social relationships.